(untitled) (Per Musi, 2023)
This article presents a critical edition of El centavo de navidad, a musical work by Colombian composer Luis Antonio Calvo (1882-1945). This composition is mentioned in music catalogues, archives, and repositories, but its score was not actually located in any of them up until now. The authors found a handwritten copy of it at the library of the School of Arts and Humanities at Instituto Tecnológico Metropolitano (Medellín, Colombia), which explains their interest in this composition. The critical edition proposed here aims to reflect on the context of the work, its cataloging, and different modifications, derived from the manuscript editing process. Manco, Moreno and Palacios apply various methodological strategies typical of critical editing —such as ecdotics, heuristic, and hermeneutics—, all combined with analysis, interpretation, and critical reflection. The result is the first edition of the previously unpublished Calvo’s manuscript, which seeks to contribute to the consolidation of his catalogue. This edition makes the composition available to researchers, musicians, and enthusiasts of Colombian music.